Pujangga (Kraton) Jawa Vs Agen dalam Pandangan Bordieu - Arsanti Wulandari (Manuskripta, 2017)
Generally, among the Javanese kingdom, there are poets who are employed specifically to produce texts or engage in the process of creating texts within the palace. These poets are the "hands" of the Kings to write down a story, advice or teachings that the King will pass on to his children or citizens. Furthermore, the texts produced are often anonymous. This indicates that writers and copywriters are still just behind the scenes. This paper will discuss the phenomenon and compare it with Bordieu's concept of agent concept which he thinks is highly influenced by habitus, capital, and strategy so that it affects the author's position and legitimacy of the results in the literary arena. This article makes the text SB 169: Babad Ngayogyakarta HB IV-V written by Tumenggung Sasra Adipura in 1869 and has been copied back in 1881 by Carik Sastra Pratama Nom, son of Patma Pratama, as the main corpus which comparated with Bordieu's concept. === Pada umumnya, di kalangan kerajaan Jawa terdapat pujangga yang dipekerjakan khusus untuk memproduksi teks atau terlibat dalam proses penciptaan teks di lingkungan istana. Pujangga-pujangga inilah yang menjadi “tangan” para Raja untuk menuliskan sebuah cerita, nasehat atau ajaran yang akan disampaikan Raja kepada anak-anaknya ataupun warganya. Lebih lanjut, teks-teks yang dihasilkan seringkali anonim. Hal ini mengindikasikan penulis dan penyalin naskah masih sekedar berperan di belakang layar. Makalah ini akan membahas fenomena tersebut dan membandingkannya dengan konsep Bordieu tentang konsep agen yang menurutnya sangat dipengaruhi oleh habitus, modal, dan strategi sehingga berdampak pada posisi pengarang dan legitimasi hasilnya dalam arena sastra. Artikel ini menjadikan teks SB 169: Babad Ngayogyakarta HB IV-V yang ditulis oleh Tumenggung Sasra Adipura pada tahun 1869 dan telah disalin kembali pada tahun 1881 oleh Carik Sastra Pratama Nom anak dari Patma Pratama sebagai korpus yang dibandingkan dengan konsep Bordieu.